2016
DOI: 10.17222/mit.2014.305
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the mechanical and corrosive properties of newly developed glass-steel composites

Abstract: This paper presents a preliminary research about a newly developed glass-steel composite created with diffusion welding of glass (C49-1) and carbon steel (St3sp). The main conclusions on the process of forming a diffusion zone during the welding of glass and steel are made. The results of quasi-static and cyclic mechanical tests and corrosion investigations are presented and interpreted on the basis of the microstructure developed during diffusion welding and described in this article. Keywords: hardening of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A composite of glass-steel was manufactured [24]: Glass C49-1 has the compositions of 67.5% SiO2, 20.3% B2O3, 3.5% Al2O, and 8.7% Na2O while carbon steel St3sp consists of 0.14~0.22% C, 0.15~0.30% Si, 0.4~0.65% Mn, 0.05% S, 0.04% P, 0.3% Cr, 0.3% Ni, 0.3% Cu, 0.08% As, and 0.01% N. The rod of the composite was heated from 20 C  to around 800 C  , then it was annealed to decrease the residual stresses. It is observed that grain size increases with the distance from the interface between the steel and glass.…”
Section: Methodsmentioning
confidence: 99%
“…A composite of glass-steel was manufactured [24]: Glass C49-1 has the compositions of 67.5% SiO2, 20.3% B2O3, 3.5% Al2O, and 8.7% Na2O while carbon steel St3sp consists of 0.14~0.22% C, 0.15~0.30% Si, 0.4~0.65% Mn, 0.05% S, 0.04% P, 0.3% Cr, 0.3% Ni, 0.3% Cu, 0.08% As, and 0.01% N. The rod of the composite was heated from 20 C  to around 800 C  , then it was annealed to decrease the residual stresses. It is observed that grain size increases with the distance from the interface between the steel and glass.…”
Section: Methodsmentioning
confidence: 99%